The Role of Transformational Leadership Management of Madrasah Principals in Improving the Accreditation of Madrasah Aliyah in Tarakan City - Muh Farhan Muh Farhan (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the role of transformational leadership management of madrasah principals in improving the accreditation of Madrasah Aliyah in Tarakan City, North Kalimantan. The study used a qualitative approach with a case study design. The research subjects were the principals of MAN Tarakan, MA Tahfidz Putri Hidayatullah Tarakan, and MA Raudatul Qur'an Tarakan. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that madrasah principals who apply transformational leadership through four main dimensions, namely exemplary behavior (idealized influence), inspirational motivation (inspirational motivation), intellectual stimulation (intellectual stimulation), and individualized consideration (individualized consideration). The implementation of this leadership has an impact on strengthening the culture of quality, increasing teacher professionalism, learning innovation, and optimizing the fulfillment of the eight National Education Standards. The strategy for improving accreditation is carried out through madrasah-based management, strengthening administration, and developing partnerships with various parties. This study confirms that the transformational leadership of madrasah principals plays an important role in continuously improving the quality and accreditation of madrasahs.